1997
DOI: 10.1111/j.1600-0765.1997.tb00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of IL‐1β, TNF‐α, IL‐8 and IL‐1ra by human polymorphonuclear leukocytes in response to lipopolysaccharides from periodontopathic bacteria

Abstract: Polymorphonuclear leukocytes (PMN) are the first cells that migrate into periodontal tissues and gingival crevices in response to invading pathogens. It was recently demonstrated that PMN have the ability to synthesize and release cytokines following appropriate stimulation, while it is not clear whether these capacities are directly related to periodontal destructive processes. We therefore investigated the amounts of the cytokines interleukin-1 beta (IL-1 beta), tumor necrosis factor alpha (TNF-alpha), IL-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 25 publications
5
118
0
6
Order By: Relevance
“…Evidence has shown that the numbers of this micro-organism are increased in patients with periodontal disease, especially those with early-onset periodontitis [3][4][5][6]. Human monocytes and polymorphonuclear neutrophils stimulated with this potential periodontopathogen have been shown to release proinflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-8 and tumour necrosis factor (TNF-AE) [7,8]. A. actinomycetemcomitans has been shown to induce alveolar bone destruction in animal models [9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that the numbers of this micro-organism are increased in patients with periodontal disease, especially those with early-onset periodontitis [3][4][5][6]. Human monocytes and polymorphonuclear neutrophils stimulated with this potential periodontopathogen have been shown to release proinflammatory cytokines, such as interleukin (IL)-1, IL-6, IL-8 and tumour necrosis factor (TNF-AE) [7,8]. A. actinomycetemcomitans has been shown to induce alveolar bone destruction in animal models [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, which factors are involved in each specific case will depend on the composition of the microbiota, i.e., the bacterial species present in the necrotic root canal. It is still worth pointing out that the potency of biological effects of the same virulence factor (e.g., LPS) can significantly vary from species to species (92,93). Thus, given the nonspecific nature of primary endodontic infections, different combinations of virulence factors will cause disease in different subjects.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α originates mainly from activated macrophages release; it is expressed in higher levels in the gingival crevicular fluid and inflamed periodontium of patients with clinical periodontium disease than in healthy people, and it also causes alveolar bone resorption. 22 As a conventional anti-inflammatory agent, minocycline hydrochloride exerts anti-inflammatory activity in macrophages and other immune cells, and these effects were independent of its antimicrobial action. It had been demonstrated having a long-term reductive effect on subgingival microorganisms, which was one of its main purposes in the course of periodontitis treatment.…”
Section: Discussionmentioning
confidence: 99%